Host‐microbe metatranscriptome reveals differences between acute and chronic infections in diabetes‐related foot ulcers. Issue 12 (22nd December 2021) - Malone, Matthew; Radzieta, Michael; Peters, Timothy J.; Dickson, Hugh G.; Schwarzer, Saskia; Jensen, Slade O.; Lavery, Lawrence A.
Abstract : Virtually all diabetes‐related foot ulcers (DRFUs) will become colonized by microorganisms that may increase the risk of developing an infection. The reasons why some ulcerations develop acute clinical infections (AI‐DRFUs) whilst others develop chronic infection (CI‐DRFUs) and the preceding host‐microbe interactions in vivo remain largely unknown. Establishing that acute and chronic infections are distinct processes requires demonstrating that these are two different strategies employed by microbes when interacting with a host. In this study, dual‐RNA seq was employed to differentiate the host‐microbe metatranscriptome between DRFUs that had localized chronic infection or acute clinical infection. Comparison of the host metatranscriptome in AI‐DRFUs relative to CI‐DRFUs identified upregulated differentially expressed genes (DEGs) that functioned as regulators of vascular lymphatic inflammatory responses, T‐cell signalling and olfactory receptors. Conversely, CI‐DRFUs upregulated DEGs responsible for cellular homeostasis. Gene set enrichment analysis using Hallmark annotations revealed enrichment of immune and inflammatory profiles in CI‐DRFUs relative to AI‐DRFUs. Analysis of the microbial metatranscriptome identified the DEGs being enriched within AI‐DRFUs relative to CI‐DRFUs included several toxins, two‐component systems, bacterial motility, secretion systems and genes encoding for energy metabolism. Functions relevant to DRFU pathology were further explored, including biofilm and bacterial pathogenesis. This identified that the expression of biofilm‐associated genes was higher within CI‐DRFUs compared to that of AI‐DRFUs, with mucR being the most highly expressed gene. Collectively, these data provide insights into the host‐microbe function in two clinically‐distinct infective phenotypes that affect DRFUs. The data reveal that bacteria in acutely infected DRFUs prioritize motility over biofilm and demonstrate greater pathogenicity and mechanisms, which likely subvert host cellular and immune pathways to establish infection. Upregulation of genes for key vascular inflammatory mediators in acutely infected ulcers may contribute, in part, to the clinical picture of a red, hot, swollen foot, which differentiates an acutely infected ulcer from that of a chronic infection.